BILINGUALISM – THE FUNDAMENTALS OF LOCAL SIGNS OF UK UZBEKISTAN-TAJIK CHEVALARY - Муҳаммадиев Нодир Рустамзода (Bright Mind Publishing, 2025)
Uzbekistan – many ethnic countries. It’s in the arms of from a hundred more various nationality and people representatives far from times since close friendly in touch living is coming International this unification, of course, their fate and life in a way related separate custom and rituals, traditions to each other to approach and even, mutually confused to leave ground created.
Keywords: Uzbekistan is a nation of yurts, two languages, Tajik and Uzbek folklore, a tradition of folklore, ceremonial folklore, Zullisonainlik, milk and sugar.